2011
DOI: 10.1103/physrevb.83.153405
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical gap generation in graphene nanoribbons: An effective relativistic field theoretical model

Abstract: We show that the assumption of a nontrivial zero band gap for a graphene sheet within an effective relativistic field theoretical model description of interacting Dirac electrons on the surface of graphene describes the experimental band gap of graphene nanoribbons for a wide range of widths. The graphene band gap is dynamically generated, corresponding to a nontrivial gapless solution, found in the limit of an infinitely wide graphene ribbon. The nanoribbon band gap is determined by the experimental graphene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
0
18
1
Order By: Relevance
“…For graphene this procedure is used to study the possibility of dynamical generation of a gap in the spectrum [30,31].…”
Section: Calculation Of the Exchange Energymentioning
confidence: 99%
“…For graphene this procedure is used to study the possibility of dynamical generation of a gap in the spectrum [30,31].…”
Section: Calculation Of the Exchange Energymentioning
confidence: 99%
“…10,11 Numerous theoretical [12][13][14][15][16][17][18][19][20][21] as well as experimental [22][23][24][25][26][27] studies have shown that this band gap depends on the GNR type, i.e., on its width as well as on the shape of its edges, e.g., zigzag or armchair, much like in carbon nanotubes. While the inverse power law for the width dependence of the band gap is found to be universal in nanoribbons of several tens of nanometers width, 22 the influence of the GNR's chiral vector becomes more and more important as the ribbons become as narrow a) Electronic mail: bronner@uni-heidelberg.de as a few carbon atoms.…”
Section: Introductionmentioning
confidence: 99%
“…This model is well suited to describe various disorder phenomena such as topological defects, doping defects or distortions of the lattice honeycomb. Within this framework, carbon nanotubes and graphene have been studied and their quantum properties have been reproduced 42,43 . In the present study, inspired by the work of [39][40][41] , we explore how charge confinement and Klein tunneling can be induced by certain types of defects, and examine how defects -modeled as 1D potential barriers -can be mapped into fermionic operators.…”
Section: Introductionmentioning
confidence: 99%